Cardiovascular manifestations of Marfan's syndrome: improved evaluation by transoesophageal echocardiography. Issue 2 (February 1993) - Simpson, I A; de Belder, M A; Treasure, T; Camm, A J; Pumphrey, C W
Abstract : OBJECTIVES–To assess the value of transoesophageal echocardiography in patients with Marfan syndrome particularly those with suspected aortic pathology or where conventional transthoracic imaging was suboptimal. DESIGN AND PATIENTS–Eleven patients with Marfan syndrome. Seven patients were studied because of suspected aortic dissection and four because of inadequate transthoracic imaging. INTERVENTION–Transoesophageal echocardiography and colour Doppler flow mapping by a 5 MHz single plane transoesophageal probe. RESULTS–Aortic dissection was identified in six patients with subsequent diagnostic confirmation in all six. No dissection was found in one patient in whom the diagnosis had been suspected clinically. Estimates of aortic root dimensions and assessment of aortic and mitral valve pathology were made in four other patients with inadequate transthoracic imaging. CONCLUSIONS–Transoesophageal echocardiography provides rapid diagnostic information in patients with Marfan syndrome with suspected aortic dissection and enhances the assessment of cardiovascular manifestations of this condition.